2016
DOI: 10.5902/2316980x20588
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da fertilidade do solo em um povoamento de <em>Eucalyptus dunnii</em> Maiden no bioma Pampa do Rio Grande do Sul

Abstract: Resumo: O monitoramento da qualidade do solo, como das propriedades químicas, pode fornecer subsídios para o manejo silvicultural e conservação do solo, visando à manutenção da produtividade de sítios florestais. O presente trabalho teve como objetivo avaliar as mudanças nos atributos químicos do solo em um povoamento de Eucalyptus dunnii, aos dois e aos cinco anos de idade, no bioma Pampa do Rio Grande do Sul. Para tanto, foram coletadas amostras de solo em cinco profundidades (0-20, 20-40, 40-60, 60-80 e 80-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The residual doses of K 2 O fertilization positively influenced soil Ca content at seventysix months after plantation with an increase in residual K 2 O dose of 96.25 kg ha −1 (Figure 2b). Dick et al [17] reported that Eucalyptus dunnii stand in a dystrophic red Ultisol at five years of growth duration showed similar soil Ca contents to those obtained at the end of our experiment with K 2 O fertilization. The average soil Ca contents were 3 mmol c dm −3 in the 0-20 cm layer (Table 1) which is considered a very low level for the development of eucalyptus [16].…”
Section: Soil Chemical Analysissupporting
confidence: 85%
“…The residual doses of K 2 O fertilization positively influenced soil Ca content at seventysix months after plantation with an increase in residual K 2 O dose of 96.25 kg ha −1 (Figure 2b). Dick et al [17] reported that Eucalyptus dunnii stand in a dystrophic red Ultisol at five years of growth duration showed similar soil Ca contents to those obtained at the end of our experiment with K 2 O fertilization. The average soil Ca contents were 3 mmol c dm −3 in the 0-20 cm layer (Table 1) which is considered a very low level for the development of eucalyptus [16].…”
Section: Soil Chemical Analysissupporting
confidence: 85%
“…Acidity and low nutrient availability are intrinsic characteristics of Pampa biome soils (STRECK et al, 2008), however, silviculture can improve soil fertility in sites where it is implanted (DICK et al, 2016b;LEITE et al, 2010). The low natural fertility of Pampa biome soils is linked to several factors, among them the lowest levels of soil organic matter, type of vegetation cover and sand and silt fraction predominance granulometric composition, which are mostly sandy (granite, sandstone) (STRECK et al, 2008).…”
Section: Soil Fertilitymentioning
confidence: 99%
“…Where: MOS = soil organic matter; V = base saturation; m = aluminum saturation; t = CTC pH=7; P = extraction by Mehlich; T = effective CTC. Table 1 shows the chemical and physical attributes of soil at 2 years of age (DICK et al, 2016). During planting, November 2008, the soil was subsoiled to 60 cm deep, with 300 kg ha -1 of natural phosphate applied to the planting line.…”
Section: Area Descriptionmentioning
confidence: 99%